PENYUSUNAN ANGGARAN PERUSAHAAN SEBAGAI ALAT MANAJEMEN DALAM PENCAPAIAN TUJUAN - ., Fadjar Harimurti (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2008)
Abstract Management of company do not far differ from management project meant to give guarantee attainment of print blue about long-range program, which include market compartment, production technology and product, officer, finance, company image, management information system, cultural of company with expense is matching with the one which budgeted previously. Process compilation of budget represent compilation process plan short-range, what is in company orient profit, election of plan based to the activity plan impact to profit. Therefore very often process compilation of budget very often conceived of by compilation plan planning profit short-run. To enable top management conduct election of activity plan affecting to do well by profit, management use technique analyze profit and cost-volume. The analysis and this profit, differential accounting information enable management to conduct election various activity alternative to be mentioned in budget. After activity plan selected to reach budget target, manager which share to execute the activity plan need resource, to enabling it reach budget target. Keywords: budget participation, compilation planning long-run profit, budget target